2019
DOI: 10.1111/ijtd.12161
|View full text |Cite
|
Sign up to set email alerts
|

Employability as a compass for career success: development and initial validation of a new multidimensional measure

Abstract: This article reports the development and initial validation of a multidimensional measure of employability based on the theoretical model of Lo Presti and Pluviano (2016). Four different studies were designed and implemented. Study 1 was a qualitative study that involved a group of 15 labour market experts and aimed at developing the items pool. In Study 2, an exploratory factor analysis of 526 employees was carried out to examine the structure of the employability measure as previously obtained. Study 3 aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 39 publications
2
40
1
Order By: Relevance
“…For example, in NEET (Not in Education, Employment or Training) population, unemployed people over 45 years or long-term unemployed people, also in favorable economic contexts. Besides, we have not hypothesized any relation between perceived employability and subjective norm, even when the social network is considered one of the components of some employability approaches ( Lo Presti et al, 2019 ). Future studies may put more emphasis on subjective norms as previous research has reported an association between the fact of receiving helpful and supportive messages from their close environment and job search intensity in Millenials ( Holmstrom et al, 2013 ; Smith, 2019 ).…”
Section: Discussionmentioning
confidence: 96%
“…For example, in NEET (Not in Education, Employment or Training) population, unemployed people over 45 years or long-term unemployed people, also in favorable economic contexts. Besides, we have not hypothesized any relation between perceived employability and subjective norm, even when the social network is considered one of the components of some employability approaches ( Lo Presti et al, 2019 ). Future studies may put more emphasis on subjective norms as previous research has reported an association between the fact of receiving helpful and supportive messages from their close environment and job search intensity in Millenials ( Holmstrom et al, 2013 ; Smith, 2019 ).…”
Section: Discussionmentioning
confidence: 96%
“…The instrument used was composed by four sub-scales adapted from the Lo Presti et al [44] (human capital and professional development, social capital, career and knowledge of the world of work).…”
Section: Methodsmentioning
confidence: 99%
“…All the items adapted by Lo Presti et al [44] in the scales were scored on five points of Likert ranging from 1 (not at all) to 5 (completely), while the skills and entrepreneurial attitudes are measured by a Likert scale ranging from 1 (not at all important) to 5 (absolutely necessary).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations